GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Transformer-Enhanced Instance Segmentation for Automated Crucian Carp Phenotyping Under Controlled Imaging Conditions - Miao Zhu; Ruohan Lu; Yi Zhou; Sisi Yuan; Qiu Xiao; Yu Deng (Fishes, 2026)
Fish phenotyping plays an important role in growth evaluation, selective breeding, and precision aquaculture. Conventional phenotypic measurement methods are labor-intensive, time-consuming, and susceptible to observer variability. To improve measurement efficiency and reproducibility, this study proposes an automated fish phenotyping framework based on Transformer-enhanced instance segmentation. Specifically, a Mask2Former decoder was integrated into the Mask R-CNN architecture to improve boundary delineation and segmentation quality. Based on segmentation outputs, phenotypic parameters, including body length, body height, and projected area, were automatically extracted using PCA-assisted orientation estimation and geometric measurement. In addition, a standardized anatomical landmark annotation framework consisting of 12 reference points was introduced to support reproducible phenotypic description and future extensible morphometric analysis. Body weight was further estimated using polynomial regression based on extracted morphological traits. Experiments were conducted using images from three crucian carp varieties under controlled imaging conditions. The proposed framework achieved 92.7% mAP and 89.4% Boundary IoU, improving segmentation performance over the baseline model. Automated measurement yielded average relative errors of 2.16% for body length and 3.85% for body height, while weight prediction achieved an R2 of 0.9479 and a mean relative error of 7.31%. These results demonstrate that Transformer-enhanced segmentation can support accurate and efficient automated phenotyping under standardized conditions and provide a foundation for future deployment in more complex aquaculture environments.

Combined organic pollutants and heavy metals distinctly alter microbial assembly and metabolism of Cynodon dactylon (L.) Pers. within industrial green belts - Junyi Yu; Shuangqiang Li; Junru Guo; Ruohan Huang; Chen Cai; Kaiming Peng; Lijun Lu; Xiangfeng Huang; Jia Liu (Journal of Environmental Sciences, 2026)

The global burden of pediatric respiratory infections attributable to long-term exposure to fine particulate matters - Xueqiu Ni; Ning Kang; Ke Huang; David Christiani; Hong Lu; Ting Yang; Ruohan Wang; Mingkun Tong; Tianjia Guan; Tao Xue (Environmental Pollution, 2025)

Inhibitory effects of potassium sorbate and ZnO nanoparticles on Escherichia coli and Staphylococcus aureus in milk-based beverage - Yuanyuan Zhang; Qianqian Yang; Feng Lu; Xiaoyang Wang; Ruohan Liang; Xiaodan Pu; Jianlei Chen; Dahai Zhang; Zhixiang Chen; Xuzhi Zhang (International Dairy Journal, 2024)

Morphological and physiological plasticity of Catalpa bungei roots under partial root-zone drought as affected by nitrogen forms - Tiantian Sun; Ruohan Ren; Mingming Xing; Qiuxiao Duan; Lang Zhao; Wenwen Yan; Yang Fang; Senyan Zhang; Hao Dong; Mengran Wang; Qimeng Heng; Wenyi Chen; et al. (New Forests, 2024)

Characterization of carbonaceous particles by single particle aerosol mass spectrometer in the urban area of Chengdu, China - Junke Zhang; Rui Wang; Chunying Chen; Yunfei Su; Luyao Chen; Wei Zhang; Yingwei Xi; Yangchun Yu; Ruiyan Pu; Minghui Lu; Ruohan Wu; Xuhui Shen (Environmental Science and Pollution Research, 2024)

Long-term exposure to the components of fine particulate matters and disability after stroke: Findings from the China National Stroke Screening Surveys - Hong Lu; Ruohan Wang; Jiajianghui Li; Mingkun Tong; Man Cao; Hengyi Liu; Qingyang Xiao; Yixuan Zheng; Yuanli Liu; Tianjia Guan; Tao Xue (Journal of Hazardous Materials, 2023)

Corrigendum to SaMT3 in Sedum alfredii drives Cd detoxification by chelation and ROS-scavenging via Cys residues [Environmental Pollution 315 (2022) 120410] - Jianqi Zhao; Ruohan Xie; Jiayu Lin; Lingling Xu; Xiaoyu Gao; Xianyong Lin; Shengke Tian; Lingli Lu (Environmental Pollution, 2023)